The Role of Military-Recreational Tourism in Solving Socio-Economic Problems (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In economically developed countries of the world, the tourism industry occupies a leading position in the economy, and its level of development, dynamics, technological, structural and other characteristics have a certain impact on economic and social progress, and the position of countries in the global world. The tourism industry in the world is developing rapidly, ranking third in terms of GDP, behind the oil industry and the automotive industry. This to some extent defines the service sector as the leading sector of the economy of developed countries.